Assessment of immune response in cattle against experimentally prepared trivalent (O, A, and Asia-1) FMD vaccine in Bangladesh - Chowdhury, Md. Mashfiqur Rahman; Hossen, Md. Liakot; Amin, Khaled Bin; Nazir, K. H. M. Nazmul Hussain; Ahmed, Sultan; Rahman, Marzia; Khan, Mohammad Ferdousur Rahman; Rahman, Md. Tanvir; Rahman, Md. Bahanur (Journal of Advanced Veterinary and Animal Research, 2015)
This research work was conducted to investigate the effects of age, sex and breed on the induction of immune response against experimentally prepared inactivated trivalent (type O, A, and Asia-1) FMD vaccine. Twenty six cattle were divided into four test groups (Group A, B, C, and D; 5 cattle in each group) and one control group (n=6) based on breed (local and cross), age (?12 months and >12 months), and sex (male and female). Test cattle were vaccinated with the experimentally prepared trivalent FMD vaccine. Pre- and post vaccinated sera from the vaccinated cattle were collected upto 63 days, and the sera were tested using liquid phase blocking enzyme linked immunosorbent assay (LPBE) that was specific for FMD serotypes O, A, and Asia-1. Antibody titers of all the pre-vaccinated serum samples were found to be under protection level. The females were found to be more protected (90%; n=9/10) as compared to males (70%; n=7/10). The titers obtained were statistically analyzed using ttest to observe the effects of age, breed and sex. It was observed that the mean values of antibody titer in cattle aging >12 months against O, A, and Asia-1 serotypes were significant (P<0.05) at 21, 49 and 63 days as compared to the values obtained from the cattle aging ?12 months. In conclusion, the local female cattle aging >12 months showed better immune response towards trivalent FMD vaccine. http://dx.doi.org/10.5455/javar.2015.b121